Bridging agroecology and food system transition frameworks: identifying shared methodological and conceptual tensions - Averbuch, Bonnie; Stone, Tiffanie; Sandén, Taru; Schwarz, Gerald; Thorsøe, Martin Hvarregaard; Bindelle, Jerome; Boeraeve, Fanny; Cassart, Pauline; Dalgaard, Tommy; Dumont, Benjamin; Herrera, Beatriz; Kambashi, Bienvenu; et al. (Frontiers Media S.A., 2026)
This perspective paper draws on insights from a 2024 symposium entitled ‘Exploring methods for researching shifts in knowledge production for agroecology transition’. The symposium critically examined emerging conceptual and methodological challenges arising from combining agroecology with living labs and research infrastructures as key instruments promoted within EU policy to strengthen Agricultural Knowledge and Innovation Systems (AKIS). Through presentations, group discussions, and iterative reflections, we identified four key tensions: structural constraints limiting farmers’ agency within living lab approaches, the problematic nature of AKIS as supposedly neutral frameworks, the oversimplification of transition frameworks as linear rather than overlapping categories, and risks of definitional dilution or cooptation. We then demonstrate that these tensions are not unique to agroecology, bridging the concepts and methods within agroecology research with those used in other fields of sustainable food system transition research, such as transdisciplinary research and sustainable transitions. This conceptual mapping of shared tensions reveals opportunities for mutual learning. Bridging these fields would help create clarity at the conceptual and methodological levels, ultimately strengthening the theoretical foundations and enabling more nuanced approaches to food system transition research.
Keywords: agricultural knowledge and innovation systems; agroecology; AKIS; living labs; research infrastructures; sustainable food system transition; sustainable transitions; transdisciplinary research